Pendekatan Pakematik untuk Meningkatkan Hasil Belajar IPA Terpadu pada Peserta Didik Kelas IX.5 SMPN 1 Tarowang - Suhardiman, Suhardiman; Armita Cahyani; Ummu Kalsum; Roni Ririn; Andi Firta Nurwafiq Azizah; Belinda Dwi Utami (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
This research is a classroom action research that aims to determine the implementation of Active, Creative, Effective, and Fun Learning Utilizing Information and Communication Technology (PAKEMATIK) and improve the learning outcomes of class IX.5 students in Integrated Science subjects with magnetism material at SMP Negeri 1 Tarowang Regency. Jeneponto with a PAKEMATIC approach. The subjects of this study were students of class IX.5, totaling 23 people. This research was carried out in two cycles with three face-to-face meetings in each cycle. The flow of this research uses the Kemmis and Mc Taggart model which consists of planning, action, observation, and reflection. The results of this study indicate that there is an increase in student learning outcomes using the PAKEMATIC approach, with results in each cycle from 52% to 86 % in cycle I and cycle II. The implication of this research is that teachers can implement the PAKEMATIC approach as an alternative to learning in the classroom so that it is not monotonous and more varied.